Influence of Undergraduates Gender on the Use of Blog for Learning in University of Ilorin Nigeria - Florence Olutunu DARAMOLA; Gboyega Ayodeji ALADESUSI (Universitas Pendidikan Indonesia Kampus Purwakarta, 2022)
The impact of undergraduate gender on the usage of blogs for learning at the University of Ilorin in Nigeria was investigated in this study. The research used survey-style descriptive research. The participants in this study were all undergraduates at the University of Ilorin. Using the Israel Model, proportional sampling procedures were employed to assign a number of responders to each school depending on their anticipated population (2012). An customized questionnaire served as the data gathering tool. With the help of statistical product and service solution (SPSS) version 20.0, descriptive and inferential statistics were employed to answer the research question and test the stated hypothesis at the 0.05 level of significance. The studies revealed that students at the University of Ilorin utilize blogs well for learning. There was no significant difference in the usage of blogs for learning by male and female students (t (362) = 0.00, p0.05). According to the findings, if appropriate technologies are used for education, learning can be boosted and teaching can be effective among undergraduates. As a result, it was suggested that all undergraduates, regardless of gender, be encouraged to use blogs for learning.